Multi-dimensional performance measurement framework for nonprofit organisations - Gowindasamy, Maniyarasi (2019)
Performance measurement is one of the major topics that can be linked to the improvement in performance management and managerial effectiveness in an organisation. It can be defined as the accomplishment of a given organisational task which involves studying a process or strategy. A non-profit organisation (NPO) is an effective change agent in socio-economic sectors and international development. Performance measurement becomes one of the vital elements in NPOs since the funding comes from various sources and there is an urgency to show the effectiveness of NPOs through performance measurement. However, even there is a clear pathway for NPOs to contribute to the well being of the society as outlines by the National Integrity Plan, there is still a lot of lacking factors to evaluate their performance which lead to the effectiveness of the organisation. This study investigates the lacking indicator and additional enabling factors and variables that could strengthen the measurement tool which later can be used as a measurement tool to suit the nature of the different NPOs in Malaysia. This study adapted variables from Garner’s (2008) goal setting theory, Reid and Smith (2000) contingency theory and Balanced Score Card. A qualitative method is used to conduct this study and a case study method is used. 16 samples are selected based on the 15 categories of NPOs as prescribed by the Registrar of Society, Malaysia (ROS).The sample is selected based on a purposive sampling. The basic selection is based on two criteria. The first criteria are the NPOs must be operating more than 5 years and second it must be operating in the area of Klang Valley and Selangor. The data are collected through a semi-structured interview which lasted about more than one hour. The contents are analyzed using the thematic analysis by merging the origination and nomination techniques. Since there is some proposed attributes/variable/factor from the different theories, they are used to stimulate the analysis. There are six important attributes of theme been identified; financial and internal process from Balanced Scorecard; empowerment, motivation and employees’ commitment from goal setting theory; leadership from contingency theory and human governance from the respondent’s view. The finding reflects that it is not necessary for NPO to rely on the scorecard attributes but there are more significant attributes such as leadership and employees' commitment. The findings provide more insight that NPOs are having constraints to implement the performance measurement because there is no guidance from the authority and they are not given the vital role to perform as NGO in Malaysia comparatively to NPOs in the developed countries. The study has reflected a new multi-dimensional framework with 7 elements; financial, internal process, human governance, leadership, empowerment, motivation and employees commitment as the new dimension tool to evaluate the performance measurement in the context of NPO. The multi-dimensional performance evaluation tool gives a wider scope on how NPO should access their own performance and is able to align towards the mission of the organisation. These variables are tested and applied in the NGO to verify its suitability and provide a positive feedback. This study has closed the gap of knowledge as this tool is developed based on Malaysia cultural and social context. This study contributes not only to NPO but also the relevant department of social welfare. It could also be integrated with NPOs so that they can play a vital role in the development of socio-economic and the well-being of the nation.